2018
DOI: 10.1002/ijc.31800
|View full text |Cite
|
Sign up to set email alerts
|

PCNA‐associated factor P15PAF, targeted by FOXM1, predicts poor prognosis in high‐grade serous ovarian cancer patients

Abstract: Activation of the FOXM1 signaling pathway and the PI3K/AKT/mTOR signaling pathway is associated with poor prognosis in ovarian cancer. In this study, we demonstrated that P15 (KIAA0101) was significantly upregulated in high-grade serous ovarian cancer (HGSOC) and that high KIAA0101 expression was associated with poor prognosis. FOXM1 transcriptionally activated KIAA0101 to drive proliferation and metastasis of ovarian cancer cells. KIAA0101 activated the PI3K/AKT/mTOR signaling pathway to inhibit cisplatin-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…By competing with PCNA binding, KIAA0101 involves in the regulation processes of DNA replication, DNA repair, and cell cycle [4,11]. Recent researches focus on its oncogenic role and indicate that KIAA0101 level is markedly increased in various types of cancer, including breast [5], adrenal [12], ovarian [13], and gastric cancer [14]. In this study, we observed an increased expression of KIAA0101 in NSCLC tissues than in the paired normal tissues as well as in NSCLC cells.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…By competing with PCNA binding, KIAA0101 involves in the regulation processes of DNA replication, DNA repair, and cell cycle [4,11]. Recent researches focus on its oncogenic role and indicate that KIAA0101 level is markedly increased in various types of cancer, including breast [5], adrenal [12], ovarian [13], and gastric cancer [14]. In this study, we observed an increased expression of KIAA0101 in NSCLC tissues than in the paired normal tissues as well as in NSCLC cells.…”
Section: Discussionmentioning
confidence: 49%
“…In the tumor setting of human gastric cancer, Zhu et al reported that increased KIAA0101 was a risk marker for recurrence [14]. As for the possible mechanism behind the pro-tumor effect, KIAA0101 was reported to be involved in tumor invasion and recurrence by promoting epithelial-to-mesenchymal transition (EMT) by Zhang et al and Jin et al [13,16]. Based on the prior literature, we speculate that KIAA0101 might partly involve in EMT in NSCLC.…”
Section: Discussionmentioning
confidence: 73%
“…The FOXM1 transcription factor, mainly expressed in the proliferative cells, is a member of the Forkhead box family of transcription factors. Recent studies have demonstrated that FOXM1 is frequently overexpressed in different kinds of cancers, including PCa, and is con rmed to be highly correlated with the proliferation and metastasis of many cancers [4][5][6][7][8]. Moreover, several studies indicated that FOXM1 overexpression conferred acquired chemotherapy tolerance through the regulation of many genes, including ATP-binding cassette genes [9][10], DNA damage repair genes [11], apoptosis-associated genes [12], cancer stem cell-related genes [13][14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…FOXM1, a transcription factor mainly expressed in proliferative cells, is part of the Forkhead box family of transcription factors. Recent studies indicate FOXM1 is commonly overexpressed in many kinds of cancers, including PCa, and its expression is highly correlated with cancer proliferation and metastasis [4][5][6][7][8]. Several studies suggest FOXM1 overexpression confers acquired chemotherapy tolerance through the regulation of numerous genes, including ATP-binding cassette genes [9][10], DNA damage repair genes [11], apoptosis-associated genes [12], cancer stem cell-related genes [13][14].…”
Section: Introductionmentioning
confidence: 99%